2017
DOI: 10.1590/0001-3765201720160865
|View full text |Cite
|
Sign up to set email alerts
|

The influence of non-steroidal anti-inflammatory drugs and paracetamol used for pain control of orthodontic tooth movement: a systematic review

Abstract: The present study aimed to perform a systematic literature review to determine if there is a non-steroidal anti-inflammatory drug (NSAID) that interferes less within tooth movement. This research was performed according to the PRISMA statement. Articles were searched in eight electronic databases (PubMed, Scopus, Embase, Web of Science, LILACS, SciELO, Google Scholar, and Open Grey). Only experimental studies on male Wistar rats were selected, which included experiments related to the influence of NSAIDs on or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
0
14
0
4
Order By: Relevance
“…In the present systematic review, we followed well‐established guidelines and conducted an exhaustive search up to June 2019 that was comprehensive and included every potentially relevant study, contrary to existing investigations focusing on specific medication categories and animal species . Moreover, the retrieved contemporary data add on the information provided in earlier systematic reviews, which did not focus specifically on the short‐term systemic administration of analgesics, that is consistent with the usual clinical practice in case of pain experienced due to orthodontic procedures .…”
Section: Discussionmentioning
confidence: 99%
“…In the present systematic review, we followed well‐established guidelines and conducted an exhaustive search up to June 2019 that was comprehensive and included every potentially relevant study, contrary to existing investigations focusing on specific medication categories and animal species . Moreover, the retrieved contemporary data add on the information provided in earlier systematic reviews, which did not focus specifically on the short‐term systemic administration of analgesics, that is consistent with the usual clinical practice in case of pain experienced due to orthodontic procedures .…”
Section: Discussionmentioning
confidence: 99%
“…It should also be used with caution in patients suffering from kidney or liver diseases [ 16 ]. Furthermore, it has been shown that tooth movement could be impaired if high concentrations of NSAIDS are used [ 30 ]; however, the patches were used only during the separator placement stage of treatment (3 days) and not for the whole duration of fixed orthodontic treatment, and thus it could not have interfered with tooth movement. It is also important to point out that the amount of naproxen in the patch was 5 mg, which was rather low (overall = 9 × 5 = 45 mg for all patches), and thus it could not have had any significant systemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Dantų judėjimą sukelia nuolat veikiančios mechaninės jėgos, kurias sukuria ortodontiniai prietaisai. Šio proceso metu, kaip minėta anksčiau, vyksta uždegiminiai pokyčiai periodonto audiniuose, kraujyje padaugėja uždegiminių mediatorių, sukeliančių skausmą [17], todėl skausmo kontrolė ortodontinio gydymo metu (ypač gydymo pradžioje) yra labai svarbi.…”
Section: Skausmas Irunclassified
“…Šie preparatai veikia kaip prostaglandinų inhibitoriai, todėl mažina sisteminį uždegiminį procesą. Prostaglandinai dalyvauja kaulo rezorbcijoje, todėl jų slopinimas gali neigiamai paveikti dantų judėjimo greitį ar sukelti dantų šaknų rezorbciją [14,17]. Jei pacientas sveikas, analgetikai pašalinami iš organizmo dar prieš prasidedant dantų judėjimui, todėl gydymo pradžioje NVNU pavartojus trumpą laiką ir mažomis dozėmis, dantų judėjimo greitis nebus paveikiamas [4,18].…”
Section: Skausmas Irunclassified